2021
DOI: 10.3390/pathogens10080971
|View full text |Cite
|
Sign up to set email alerts
|

Three Immunocompetent Small Animal Models That Do Not Support Zika Virus Infection

Abstract: Zika virus (ZIKV) is a mosquito-borne flavivirus that is primarily transmitted to humans through the bite of an infected mosquito. ZIKV causes disease in infected humans with added complications of Guillain-Barré syndrome and birth defects in infants born to mothers infected during pregnancy. There are several large immunocompetent animal models for ZIKV including non-human primates (NHPs). NHP models closely reflect human infection; however, due to sample size restrictions, investigations into the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Finally, using nLuc-ZIKV reporter to perform an in vivo infection study in immunecompetent guinea pigs, we showed that a subset of the guinea pigs inoculated with nLuc-ZIKV displayed increased bioluminescence on PID 3 compared to sham controls (Figure 5). The variability in response depending on viral strain, age, dose, and laboratory where the study was performed has been reported in this species [16,[27][28][29] and is also likely the case in the human population. Using these variants in animal models highly susceptible to ZIKV infection, such as mouse knockout strains lacking interferon responses, may provide a more robust model for studying this infection using live imaging.…”
Section: Discussionmentioning
confidence: 66%
“…Finally, using nLuc-ZIKV reporter to perform an in vivo infection study in immunecompetent guinea pigs, we showed that a subset of the guinea pigs inoculated with nLuc-ZIKV displayed increased bioluminescence on PID 3 compared to sham controls (Figure 5). The variability in response depending on viral strain, age, dose, and laboratory where the study was performed has been reported in this species [16,[27][28][29] and is also likely the case in the human population. Using these variants in animal models highly susceptible to ZIKV infection, such as mouse knockout strains lacking interferon responses, may provide a more robust model for studying this infection using live imaging.…”
Section: Discussionmentioning
confidence: 66%
“…ZIKV is detectable by RT-PCR in the spleen, the brain, and several other tissues [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. In contrast, non-susceptible species have little or no virus detectable in their blood during the first three days after inoculation, and ZIKV is not detectable in their tissues [ 64 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%